A vitivinicultura e o desenvolvimento do enoturismo de Bituruna, Paraná - Sampietro, Leidh Jeane (My University, 2016)
This research investigated the relationship between viticulture and the development of wine tourism in the municipality of Bituruna, state of Paraná. Being an essentially farming activity, viticulture includes the cultivation and production of grapes for wine production and derivatives. The wine tourism, tourism related to wine, has been developing in Brazil and causes the need to provide goods and services to tourists. Bituruna in grape growing and winemaking began between the decades from 1930 and 1950, the touristification space has been happening slowly. The research is characterized as descriptive qualitative, conducted through the analysis of bibliographic references and interviews with leading wine producers of the municipality, the public and private sector managers, and community representatives. The results indicate that the wine industry is a promising activity, but the wine tourism is incipient by the lack of specific plans to contribute to their full development . The wine tourism in Bituruna can offer the possibility of socioeconomic and cultural development , as long as it better planned.
Este trabalho de pesquisa busca aprofundar a relação entre vitivinicultura e o desenvolvimento do enoturismo no município de Bituruna, estado do Paraná. Sendo uma atividade essencialmente agrícola, a vitivinicultura engloba o cultivo e produção das uvas para produção de vinhos e derivados. O enoturismo, atividade turística associada ao vinho, vem se desenvolvendo no território brasileiro e ocasiona a necessidade de se disponibilizar produtos e serviços ao turista. Em Bituruna o cultivo da uva e a elaboração de vinhos teve início entre as décadas de 1930 e 1950, a turistificação do espaço vem ocorrendo lentamente. A pesquisa se caracteriza como qualitativa descritiva, realizada por meio da análise de referenciais bibliográficos e entrevistas com os principais produtores de vinho do município, gestores do setor público e privado, além de representantes comunitários. Os resultados indicaram que a vitivinicultura é uma atividade promissora, mas o enoturismo é incipiente pela falta de planos específicos que contribuam com o seu pleno desenvolvimento. O enoturismo em Bituruna oferece possibilidade de desenvolvimento socioeconômico e cultural, desde que melhor trabalhado.
Keywords: Enoturismo - Bituruna (PR); Vitivinicultura; Turismo; Uvas - Cultivo; Vinho e vinificação; Wine tourism - Bituruna (Brazil); Tourist trade; Viticulture; Wine and wine making